2012
DOI: 10.1021/jf2048492
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Benzoxazinoids in Rye Bread Are Absorbed and Metabolized in Pigs

Abstract: Recently, bioactive benzoxazinoids were discovered in cereal grains and bakery products. In this study, we studied the uptake, distribution, and metabolism of these secondary metabolites using a pig model. Twelve benzoxazinoid compounds and their 4 transformation products were quantified in the pigs' diets and biofluids using high-performance liquid chromatography coupled to electrospray ionization triple quadrupole mass spectrometry. The 2-β-D-glucopyranosyloxy-4-hydroxy-1,4-benzoxazin-3-one (DIBOA-glc) was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 51 publications
6
56
2
Order By: Relevance
“…Recently, there were several targeted, quantitative approaches on the characterization of bioavailability and absorption of dietary benzoxazinoids in rats (17), pigs (16), and humans (18). In rats, 3 benzoxazinoid compounds (HBOA, HBOA glucose, and DIBOA glucose) were detected in plasma 3 h after feeding (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there were several targeted, quantitative approaches on the characterization of bioavailability and absorption of dietary benzoxazinoids in rats (17), pigs (16), and humans (18). In rats, 3 benzoxazinoid compounds (HBOA, HBOA glucose, and DIBOA glucose) were detected in plasma 3 h after feeding (17).…”
Section: Discussionmentioning
confidence: 99%
“…Several compounds of the benzoxazinoid class were detected in the plasma and urine of pigs (16) and rats (17) and in a human study showing the postprandial appearance of benzoxazinoids in circulation and urine (18). In addition to these studies using targeted, quantitative assays, a recent nontargeted metabolite profiling study indicated phenylacetamides as the predominant urine metabolites of benzoxazinoids (19).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the presence of these allelochemicals in grain means that they are involved in mammalian and human digestion. Absorption, transformation and excretion have been studied in pig and, in this context, new routes of transformation such as reduction, oxidation, demethoxylation and deglycosylation were described . By contrast, it was found that 2‐β‐ d ‐glucopyranose HBOA 2‐hydroxy‐1,4‐benzoxazin‐3‐one derivative is the principal metabolite in human plasma and urine when 2‐β‐ d ‐glucopyranose DIBOA 2,4‐Dihydroxy‐1,4‐benzoxazin‐3‐one derivative is the principal constituent in the diet.…”
Section: Chemistrymentioning
confidence: 99%
“…Ingestion of rye bread which naturally contains a mixture of BXDs has revealed some aspects of BXD metabolism in mammals. For example, in rats and pigs, glucoside hydrolysis, hydroxamic acid reduction to the corresponding lactam, and aglucone conjugation to glucuronic acid were important metabolic reactions (Adhikari et al 2012a, b). In humans, hydroxamic acid reduction and aglucone conjugation with glucuronic acid and sulfate were observed (Adhikari et al 2013).…”
Section: Metabolism Of Bxdsmentioning
confidence: 99%